2012
DOI: 10.1007/s00167-012-1977-7
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition and degeneration of articular cartilage

Abstract: PurposeTo determine the importance of synovial fluid (SF) or subchondral bone marrow (BM) as nutrition sources in cartilage degeneration.MethodsNinety-five-month-old male rabbits were randomly divided into 5 groups according to sources of nutrition: SFBM-both; BM-only; SF-only; None-SFBM; and Free plug (unrestricted). Nutrition to 4-mm-diameter cylindrical osteochondral plugs created on the trochlea of the distal femurs was obstructed by Polyvinyl Chloride (PVC) cap. Cartilage changes were assessed after 4, 8,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(36 citation statements)
references
References 32 publications
1
33
0
2
Order By: Relevance
“…Recently, several studies demonstrated that nutrient supply of natural articular cartilage mainly comes from synovial fluid [26]. Our study shows that, IV bioreactor fluid component analysis showed that protein, glucose, and HA were close to synovial fluid than serum ( Table 2).…”
Section: Discussionsupporting
confidence: 57%
“…Recently, several studies demonstrated that nutrient supply of natural articular cartilage mainly comes from synovial fluid [26]. Our study shows that, IV bioreactor fluid component analysis showed that protein, glucose, and HA were close to synovial fluid than serum ( Table 2).…”
Section: Discussionsupporting
confidence: 57%
“…In fact, Wang et al [20] found that synovial fluid, but not SB, provides enough nutrients to maintain cartilage structure and function in mature rabbits.…”
Section: Transporting Lipids Through the Cartilagementioning
confidence: 99%
“…Our results proved that there was a decline in the diffusion of Visipaque with aging. Thereby, the lack of enough metabolite transport from the cartilage surface might result in blood vessel invasion and subchondral bone advancement 39 .…”
Section: Discussionmentioning
confidence: 99%